The role of the microRNA-controlled modules in the regulatory network of seedling development - Pierdoná, Flaviani Gabriela (2024)
The initial development of plants is crucial to their proper establishment. The post-embryonic development is marked by hypocotyl elongation and has a fine regulatory network evolving environment, phytohormones, and gene expression. The brassinosteroids (BR) are a class of phytohormones acting in the hypocotyl elongation. It mainly induces the BRASSINAZOLE RESISTANTE 1 (BZR1) which regulates downstream genes that promote cell expansion. BZR1 also binds to PHYTOCHROME INTERACTING FACTORs (PIFs) to control common targets interconnecting BR and light signals into the regulatory network. When seeds germinate in the dark, when PIFs are de-repressed from the phytochrome regulation, the skotomorphogenesis is activated. During this developmental phase, the upper part of the hypocotyl bends down to form the apical hook to protect the shoot apical meristem and the cotyledons. Importantly, an asymmetric accumulation of auxin in the top cells of the hypocotyl is a prerequisite to the apical hook development. Puzzling, localized auxin maxima represses local cell expansion by indirectly inhibiting the small auxin up-regulated RNA (SAUR) gene family. Interestingly, SAURs are also controlled by the MAD-BOX gene FRUITFULL (FUL) to repress the apical hook opening. During the Arabidopsis transition from juvenile to adult phase, FUL is directly activated by some members of the SQUAMOSA PROMOTER BINDING PROTEIN-LIKE (SPL) family of transcription factors. Several SPL genes are targets of the microRNA156 (miR156), suggesting that this miRNA may regulate hook formation. In fact, mutations in core enzymes of the miRNA biogenesis, such as SERRATE (SE) or DICER-LIKE 1 (DCL1), result in shorter hypocotyls and more closed apical hooks during skotomorphogenesis. A similar phenotype was observed in seedlings carrying mutations in several MIR156 genes. In this work, we first reviewed the state of the art in the skotomorphogenesis and apical hook development field; following, we show our initial observations that the miR156/SPL9 interacts with BR in the control of cell expansion during hypocotyl development; finally, we present in a manuscript format our results that support the finding of a new molecular circuity involving Auxin/miR156-SPL9/FUL/SAUR regulation of the Arabidopsis apical hook development, which seems to be conserved in crops such as tomato (Solanum lycopersicum).